Distal Endoscopic Attachments - Desai, Pankaj N.; Patel, Chintan N.; Kabrawala, Mayank; Nanadwani, Subhash; Mehta, Rajiv; Prajapati, Ritesh; Patel, Nisharg; Sethia, Mohit (Journal of Digestive Endoscopy, 2022)
Endoscopy is an evolving science and the last two decades has seen it expand exponentially at a pace unapparelled in the past. With the advancement in new procedures like image-enhanced endoscopy, magnifying endoscopy, third space endoscopy, and highly advanced endoscopic ultrasound procedures, endoscopic accessories are also evolving to cater the unmet needs. Endoscopic cap or distal attachment cap is a simple but very important accessory in the endoscopists' armamentarium which has changed the path of endoscopic procedures. It has so far been used commonly mostly for variceal ligation and endoscopic mucosal resections for colorectal polyps. But the horizon of its use has expanded in the recent years for difficult clinical scenarios like providing stability to the endoscope, overcoming blind spots during screening colonoscopies, maintaining clear field of vision during endotherapy of gastrointestinal bleeding, and during magnification endoscopy for lesion characterizations and so on. These caps are of different shapes, sizes, colors, and material depending on manufacturers and their implications while performing varied endoscopies. This review summarizes the clinical utilities of the cap in diagnostic as well as therapeutic endoscopy and its expanding indications of use.
Keywords: distal attachment cap; EMR; endoscopy; ESD; magnification endoscopy; POEM